Konservative Hämophiliebehandlung unter Berücksichtigung der Optimierung und Standardisierung - Seuser, A.; Wallny, T.; Kurth, A.; Berdel, P. (Hämostaseologie, 2010)
Rehabilitation and physical therapy in the sense of functional health is based on the international classification of function. It takes in two considerations: function and structure of the body and their influence on personal and social activity. The integrative concept of joint function translates the basic concept of body function and structure on to the motion of the locomotive system. Stability needs motoric control. Motoric control and the integrated neural components are to be influenced through regulation of muscle tonus (massage, manual therapy, medical training therapy, electrotherapy and thermotherapy). The stability of the joint is controlled by the passive components. Passive structures are optimised through passive therapies like joint mobilisation. Active components of joint function are optimised through activation (medical training therapy, stabilisation, mono or multisegmental levels). Emotional and neuronal components can be triggered through kinesthetic exercises like PNF, Jacobsen relaxation, biofeedback training, mental training. Exact examination of the locomotive system will help finding all symptoms. This is how we individualise the therapy of symptoms and structures. The motion pattern generator shows us how to use the possibilities of functional influence on the motion pattern. We have a lot of afferent signals that need individualised functional therapy. This is why we need functional measurements like motion analysis on the basis of ultrasound. An other tool is the kinetic superficial EMG measurement of muscle function. We can use it to determine the status of the joint and it will lead to therapeutical decisions. All functional measurements will help to improve quality control of the physical therapy process. Even if the haemophilic patient is healthy he is not fit at all. Measurements of fitness will help us to improve special skills and establish the human being as a subject in society and environment. The main skill to be improved in haemophiliacs is coordination, strength of the stomach muscles and the vastus medialis and the flexibility of the hamstrings.
Keywords: Hemophilia; conservative treatment; motion analysis; kinetic superficial EMG